Effects of the proportion of two different cross-linkers on the material and biological properties of enzymatically degradable PEG hydrogels. (February 2020) - Liu, Siju; Cao, Hong; Guo, Renqi; Li, Heling; Lu, Cuifen; Yang, Guichun; Nie, Junqi; Wang, Feiyi; Dong, Nianguo; Shi, Jiawei; Shi, Feng
Abstract: A series of enzymatically degradable PEG hydrogels with tunable degradability were prepared by changing the proportions of two cross-linkers, enzymatically degradable cross-linker matrix metalloproteinase (MMP) degradable peptide and non-degradable cross-linker PEG-dithiol, and the effects of the proportion of two cross-linkers on the other properties of PEG hydrogels were also investigated. As the content of the degradable cross-linker increased, their mechanical properties decreased, but their swelling rate gradually increased. LIVE/DEAD cell staining and CCK-8 assay indicated that PEG hydrogels have high biocompatibility and low cytotoxicity, and as the content of the degradable cross-linker increased, the proliferation of cells is more favorable. Furthermore, adipogenic differentiation and osteogenic differentiation assays showed that BMSCs 3D-capsulated in PEG hydrogels can proliferate and then differentiate into osteoblasts or adipocytes, and as the content of degradable cross-linker increased, calcium nodules and the number of fat cells increased. These results demonstrate that the proportions of two cross-linkers have an effect on the physical, chemical and biological properties of PEG hydrogels, and these PEG hydrogels could be used as tissue engineering scaffold materials. Highlights: A series of PEG hydrogels with tunable degradability were prepared by changing the proportions of two cross-linkers. The proportions of two cross-linkers have an effect on the physical, chemical and biological properties of PEG hydrogels.T. These PEG hydrogels can be used as tissue engineering scaffold materials.